Mathematical Literacy with Islamic Nuances Based on Prospective Mathematics Teachers Personality - Eka Resti Wulan; Fidia Astuti (Universitas Syiah Kuala, 2022)
Mathematical literacy is crucial to understand phenomena and good decision-making in real life. This study aims to describe aspects of Islamic nuanced mathematical literacy in prospective teachers, which were viewed from the four personalities of Keirsey. This qualitative descriptive research used a questionnaire of MTBI personality types and a mathematical literacy test with Islamic nuances. The subjects are students in the 7th semester of the mathematics education program at an Islamic university in Kediri City, East Java, Indonesia. The findings showed that rational and idealist subjects could fulfill the